Psychosocial problems: what help do rural and urban patients want from their family physicians? - Rosenberg, E E (1987)
We surveyed 399 patients of family physicians in two rural Canadian towns to determine what help with 30 psychosocial problems they wanted from their physicians. The patients completed a self-administered questionnaire in which they could choose from four levels of physician involvement: no involvement, knowledge of the problem but no help, knowledge of the problem and referral to a specialist, and treatment by the physician. Half of the patients wanted help with life-cycle problems, and over half desired treatment for sleeping problems, anxiety and depression. However, close to 50% of the patients desired no help for interpersonal problems, and over 50% wished to see a specialist for help in coping with a physical illness and long-term pain. Interestingly, English-speaking patients wanted significantly more physician involvement than did French-speaking patients. The results were similar to those of an earlier study of urban patients. Implications for family medicine training are discussed.